ESP Business English: The Proposed Students’ Workbook Used for Teaching Bahasa Inggris Bisnis at D3 Accounting of Economics & Bussiness Faculty at UNMER Malang - Yasmin Farani (Universitas Merdeka Malang, 2017)
This paper was written concerning with the needs of teaching materials for MK Bahasa Inggris Bisnis (2 credits subject taught once a week and in 100 minutes in each meeting) taught at D3 Accounting of Economics and Business Faculty. It is an Educational Research and Development since it is a qualitative research that aims to develop teaching materials. The writers use materials development procedure adapted from the framework of components of course development processes proposed by Graves (1996). The primary instruments are the researchers themselves and the secondary ones are questionnaires and interview. The products of the research are in the form of a workbook.